Wearable Tactile Sensors: Gelatin Methacryloyl‐Based Tactile Sensors for Medical Wearables (Adv. Funct. Mater. 49/2020). (1st December 2020) - Li, Zhikang; Zhang, Shiming; Chen, Yihang; Ling, Haonan; Zhao, Libo; Luo, Guoxi; Wang, Xiaochen; Hartel, Martin C.; Liu, Hao; Xue, Yumeng; Haghniaz, Reihaneh; Lee, KangJu; et al.
Abstract : In article number 2003601, Shiming Zhang, Libo Zhao, Ali Khademhosseini, and co‐authors demonstrate a GelMA hydrogel biosensor capable of monitoring various human physiological signals. The device shows excellent stability. Robust chemical bonding and a reliable encapsulation approach are introduced to overcome detachment and water evaporation issues in hydrogel biosensors. The presented method could be a universal strategy to improve the performance and stability of hydrogel biosensors.